2002
DOI: 10.1089/10430340252939050
|View full text |Cite
|
Sign up to set email alerts
|

Effective Retrovirus-Mediated Gene Transfer in Normal and Mutant Human Melanocytes

Abstract: Melanocytes represent the second most important cell type in the skin and are primarily responsible for the pigmentation of skin, hair, and eyes. Their function may be affected in a number of inherited and acquired disorders, characterized by hyperpigmentation or hypopigmentation, consequent aesthetic problems, and increased susceptibility to sun-mediated skin damage and photocarcinogenesis. Nevertheless, the possibility of genetically manipulating human melanocytes has been hampered so far by a number of limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The macromelanosomal phenotype suggests a defect in melanosome biogenesis, however it also displays variable expressivity in vivo (Garner and Jay, 1980; O’Donnell et al, 1976; Schnur et al, 1998; Wong et al, 1983) and in vitro , since giant melanosomes were observed in melanocytes obtained from Oa1 -KO mice, but not human patients (Palmisano et al, 2008; Schiaffino et al, 2002). It is possible that in different pathological conditions the deficiency of OA1 manifests with alternative phenotypes, which could nevertheless provide insights into the function of the receptor.…”
Section: Oa1 and Albinismmentioning
confidence: 99%
See 1 more Smart Citation
“…The macromelanosomal phenotype suggests a defect in melanosome biogenesis, however it also displays variable expressivity in vivo (Garner and Jay, 1980; O’Donnell et al, 1976; Schnur et al, 1998; Wong et al, 1983) and in vitro , since giant melanosomes were observed in melanocytes obtained from Oa1 -KO mice, but not human patients (Palmisano et al, 2008; Schiaffino et al, 2002). It is possible that in different pathological conditions the deficiency of OA1 manifests with alternative phenotypes, which could nevertheless provide insights into the function of the receptor.…”
Section: Oa1 and Albinismmentioning
confidence: 99%
“…It is possible that in different pathological conditions the deficiency of OA1 manifests with alternative phenotypes, which could nevertheless provide insights into the function of the receptor. For instance, primary cultures of human melanocytes from patients with ocular albinism showed no macromelanosomes, but a striking prevalence of mature over immature melanosomes, compared to wild-type or OA1-transduced cells (Schiaffino et al, 2002). Similarly, transient OA1 downregulation in MNT1 cells did not result in the formation of classical macromelanosomes (Giordano et al, 2009).…”
Section: Oa1 and Albinismmentioning
confidence: 99%
“…This time interval allows accumulation of the tracer into the lateendocytic pathway, particularly into lysosomes, because, in these chase conditions, its staining overlaps extensively with DAMP and LAMP1 (data not shown). In melanocytes, the endogenous OA1 has been localized to late endosomes and lysosomes (Samaraweera et al, 2001) and to melanosomes (Schiaffino et al, 1996;Schiaffino et al, 1999;Schiaffino et al, 2002;Basrur et al, 2003); however, quantitative studies with multiple markers have never been performed.…”
Section: Oa1 Localizes To Lysosomes In Hela Cells and To Lysosomes Anmentioning
confidence: 99%
“…This applies especially to gene therapy approaches that might be able to deliver the wild-type OA1 protein to the RPE of the affected patients, thus improving in general their visual acuity by enhancing foveal differentiation. Indeed, although essentially an issue for future applications, this has already being tested in an in-vitro gene therapy approach with cultured melanocytes from ocular-albinism patients, where the phenotype has been rescued using infection with a retrovirus carrying the wild-type OA1 protein (Schiaffino et al, 2002).…”
Section: Discussionmentioning
confidence: 99%